Combined use of arginase II inhibitors and tadalafil for the correction of monocrotaline pulmonary hypertension - Ivan S. Koklin; Lyudmila M. Danilenko (Belgorod National Research University, 2019)
Introduction: The concept of the regulatory role of endothelium in the pathogenesis of pulmonary hypertension (PH) is fundamental. Research objective: To study the protective effects of the selective arginase II inhibitors L207-0525 and L327-0346 in combination with tadalafil in a monocrotaline model of pulmonary hypertension in rats. Materials and methods: Monocrotaline-induced pulmonary hypertension was simulated in 10 animals by a subcutaneous injection of an alcohol-water solution of monocrotaline (MCT) in the dose of 60 mg/kg. Seven days after the injection of MCT, the administration of L207-0525 and L327-0346 in the doses of 1 mg/kg and 3 mg/kg was started. The compounds were administered intragastrically once a day for 21 days. Results and discussion: It was found that L207-0525 and L327-0346 in the dose of 3 mg/kg and tadalafil in the dose of 1 mg/kg prevented the development of pulmonary hypertension, which was expressed in a statistically significant decrease in the coefficient of endothelial dysfunction (CED, prevention of an increase in systolic pressure in the right ventricle, as well as Fulton, RV/BW and WT indices. The greatest activity was shown by L207-0525 and L327-0346 in the dose of 3 mg/kg in combination with tadalafil in the dose of 0.1 mg/kg. Conclusions: The received results suggest the dose-dependent protective activity of selective arginase II inhibitors L207-0525 and L327-0346 and the development of the additive effect of their combined use with low doses of PDE-5 inhibitor tadalafil in relation to the development of monocrotaline pulmonary hypertension.